Tumor-Related Exosomes Contribute to Tumor-Promoting Microenvironment: An Immunological Perspective - Wuzhen Chen; Jingxin Jiang; Wenjie Xia; Jian Huang (Journal of Immunology Research)
Exosomes are a kind of cell-released membrane-form structures which contain proteins, lipids, and nucleic acids. These vesicular organelles play a key role in intercellular communication. Numerous experiments demonstrated that tumor-related exosomes (TEXs) can induce immune surveillance in the microenvironment in vivo and in vitro. They can interfere with the maturation of DC cells, impair NK cell activation, induce myeloid-derived suppressor cells, and educate macrophages into protumor phenotype. They can also selectively induce effector T cell apoptosis via Fas/FasL interaction and enhance regulatory T cell proliferation and function by releasing TGF-β. In this review, we focus on the TEX-induced immunosuppression and microenvironment change. Based on the truth that TEXs play crucial roles in suppressing the immune system, studies on modification of exosomes as immunotherapy strategies will also be discussed.